Persistence and adherence to rivastigmine in patients with dementia: Results from a noninterventional, retrospective study using the National Health Insurance research database of Taiwan - Chang, Chee-Jen (Alzheimers Dement (N Y), 2018)
INTRODUCTION: The objective of the study was to assess adherence and persistence of patients treated with rivastigmine versus donepezil. METHODS: Persistence was calculated as the time from the first prescription date of rivastigmine/donepezil until discontinuation/medication switch/end of available data, whichever occurred first. Adherence was calculated as proportion of days covered and medication possession ratio. RESULTS: A majority of patients persisted on 4.5 and 6 mg of rivastigmine for 429 and 468 days, respectively, versus 443 and 441 days for patients receiving 5 and 10 mg of donepezil daily, respectively. Patients who initially received 1.5 mg of oral rivastigmine required a shorter time to reach a stable dose compared with those who initiated treatment at a higher dose of rivastigmine. Patients at a stable dose of 4.5 or 6 mg of rivastigmine were observed to persist longer than those at a lower dose of rivastigmine and donepezil. DISCUSSION: Although results indicate significant difference in persistence between rivastigmine and donepezil groups, clinical significance remains undetermined.